HDAC6: A Key Link Between Mitochondria and Development of Peripheral Neuropathy - Krystal English; Krystal English; Michelle Craig Barton; Michelle Craig Barton (Frontiers in Molecular Neuroscience, 2021)
Peripheral neuropathy, which is the result of nerve damage from lesions or disease, continues to be a major health concern due to the common manifestation of neuropathic pain. Most investigations into the development of peripheral neuropathy focus on key players such as voltage-gated ion channels or glutamate receptors. However, emerging evidence points to mitochondrial dysfunction as a major player in the development of peripheral neuropathy and resulting neuropathic pain. Mitochondrial dysfunction in neuropathy includes altered mitochondrial transport, mitochondrial metabolism, as well as mitochondrial dynamics. The mechanisms that lead to mitochondrial dysfunction in peripheral neuropathy are poorly understood, however, the Class IIb histone deacetylase (HDAC6), may play an important role in the process. HDAC6 is a key regulator in multiple mechanisms of mitochondrial dynamics and may contribute to mitochondrial dysregulation in peripheral neuropathy. Accumulating evidence shows that HDAC6 inhibition is strongly associated with alleviating peripheral neuropathy and neuropathic pain, as well as mitochondrial dysfunction, in in vivo and in vitro models of peripheral neuropathy. Thus, HDAC6 inhibitors are being investigated as potential therapies for multiple peripheral neuropathic disorders. Here, we review emerging studies and integrate recent advances in understanding the unique connection between peripheral neuropathy and mitochondrial dysfunction through HDAC6-mediated interactions.